Mammography screening: an incremental cost effectiveness analysis of two view versus one view procedures in London. Issue 1 (February 1995) - Bryan, S; Brown, J; Warren, R
Abstract : STUDY OBJECTIVE–To compare the costs and effects of routine mammography screening by a single mediolateral-oblique view and two views (mediolateral-oblique plus craniocaudal) of each breast. DESIGN–A cost effectiveness analysis of a prospective non-randomised trial comparing one and two view mammography screening was carried out at St Margaret's Hospital, Epping. All women in the study had two view mammography. The mediolateral-oblique view was always the first image read by the radiologist. After reading the films for a clinic session, the same radiologist then went back and read both the mediolateral-oblique and craniocaudal views together. Each set of films was read by two radiologists. The main outcome measures were recall rates, number of cancers detected, screening and assessment costs, and cost effectiveness ratios. SUBJECTS–A total of 26, 430 women who attended for breast screening using both one and two view mammography participated. A sample of 132 women attending for assessment provided data on the private costs incurred in attending for assessment. RESULTS–There was a reduction in the recall rate from 9.1% (2404 of 26, 430) after one view screening to 6.7% (1760 of 26, 430) after two view screening. The results also suggest that for every 10, 000 women screened an additional five cancers would be detected earlier with two view screening. The additional health service screening cost associated with two view screening was estimated to be 3.63 pounds: the costs associated with one and two view screening policies were estimated to be 41.49 pounds and 32.99 pounds respectively. Private costs incurred were estimated to be 0.35 pounds per woman screened and 32.75 pounds per woman assessed. Two cost effectiveness ratios were calculated: an incremental health service cost per additional cancer detected of 4129 pounds and an incremental health service plus private cost per additional cancer detected of 2742 pounds. The sensitivity analysis suggested that the results were sensitive to relatively large changes in a number of parameters. These included screening costs, assessment costs, equipment life, and recall rates. CONCLUSIONS–Use of two view screening increased early cancer detection and also costs. The reduction in the recall rate with two views was not sufficiently large to make the cost of two view screening neutral. While these results are not completely generalisable, a framework is provided to allow other centres to estimate the cost effectiveness of two view screening in their locality.